2019
DOI: 10.1002/jgh3.12224
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of marked elevations of alanine aminotransferase >1000 IU/L in an Australian cohort

Abstract: Background and Aim Marked elevations of alanine aminotransferase (ALT) are caused by a limited number of underlying pathologies, including hepatic ischemia, drugs/toxins, viral hepatitis, and—rarely—autoimmune hepatitis. The aim of this study was to determine the relative incidence of pathologies resulting in ALT greater than 1000 IU/L and factors predicting clinical outcomes in an Australian cohort. Methods A retrospective cohort study of all adult patients with ALT levels greater than 1000 IU/L between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In clinical practice, it is assumed that a severe rise in transaminases is caused by ischemic, viral, or toxic hepatitis [ 3 ]. However, in an observational study, Campos et al found pancreaticobiliary lithiasis as the most common underlying etiology of transaminase elevation 15 times above normal limit, while Con et al identified biliary obstruction as the fourth leading cause of ALT elevation greater than 1000 units/L [ 3 , 5 ]. Two recently published meta-analysis by Mohamed et al also reported biliary pathologies as the fourth leading cause of AST or ALT elevation greater than 1000 units/L, with a reported frequency of AST/ALT elevation greater than 1000 units/L between 6 and 9.6% in choledocholithiasis patients [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, it is assumed that a severe rise in transaminases is caused by ischemic, viral, or toxic hepatitis [ 3 ]. However, in an observational study, Campos et al found pancreaticobiliary lithiasis as the most common underlying etiology of transaminase elevation 15 times above normal limit, while Con et al identified biliary obstruction as the fourth leading cause of ALT elevation greater than 1000 units/L [ 3 , 5 ]. Two recently published meta-analysis by Mohamed et al also reported biliary pathologies as the fourth leading cause of AST or ALT elevation greater than 1000 units/L, with a reported frequency of AST/ALT elevation greater than 1000 units/L between 6 and 9.6% in choledocholithiasis patients [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%